Success Factors for e-Learning Satisfaction during COVID-19 Pandemic Lockdown - Nurhizam Safie Mohd Satar; Azizan Morshidi; Omkar Dastane (2020)
The research investigates effect of IT characteristicsfactors on students’ e-learning satisfaction during the period of COVID 19 pandemic lockdown. Selected factors of IT characteristics are IT complexity, IT pace change and IT presenteeism. The study also investigatesmediating role of perceived value as a second order construct comprising of perceived ease of use, perceived behavioural control and perceived usefulness. The data was collected from 470 student sample selected using convenience sampling through online questionnaire in Malaysia during Movement Control Order (lockdown) period when universities moved classes to online learning platforms. The data was then subjected to purification, normality and reliability assessment followed by confirmatory factor analysis, validity assessment and finally structural equation modelling using IBM SPSS AMOS 24.0. The findings show that all three factors have significant impact on e-learning satisfaction. IT complexity has the most prominent impact on e-learning satisfaction among selected variables. In addition, perceived value fully mediates relationship among all three independent variables and learning satisfaction. Implications, limitations and future research avenues are then discussed.